IDENTIFIKASI KEMAMPUAN KERJA APARAT DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN PUBLIK (Studi Kasus di Kecamatan Abeli Kota Kendari) - Muhammad Yusuf; Wempi Banga (Journal Publicuho, 2019)
The purpose of this study is expected to be useful for the development of the concept of quality public services in order to develop lecture material in the field of public administration, and also useful as a contribution of thought to the local government of Kendari City in the form of community service.The population in this study were 203 people, consisting of elements from the village and sub-district government officials and community elements who had received custody services in the last three months (April, May and June 2009). The sample size is calculated according to Yamne formula, by setting precision of 5% and a degree of trust of 95%, then the sample obtained by respondents is 158 people. The sampling of each element is based on a proportional formula then drawn by a simple random sampling technique from each element. Data collection/information, breastfeeding using questionnaires and interviews. Data analysis was performed using tabulation tools, percentages and averages, which were then interpreted to determine the level of influence of variable dimensions of the apparatus' ability on the variable quality of public services in the Abeli District of Kendari City.The results of this study indicate that the condition of the ability of government officials to work in public services in the Abeli District of Kendari City can be illustrated through 3 (three) basic dimensions of apparatus capacity, as follows: (b) Professional technical training possessed by apparatus is classified as high. (c) The work experience of the officers, in general, is less useful because their placement is not relevant to their work experience. With these conditions, the influence of the ability of government officials on the quality of public services in the Abeli District of Kendari City is generally low.